Effectiveness of Phyllanthus niruri and Andrographis paniculata Extracts on Egg Quality in Laying Hens with Avian Pathogenic Escherichia coli - Hidanah, Sri; Sabdoningrum, Emy Koestanti; Chusniati, Sri; Nurliyani, Nurliyani; Khairullah, Aswin Rafif; Nayan, Nazri (Jurnal Medik Veteriner, 2023)
Providing sufficient and high-quality eggs plays an essential role in accommodating food safety and food security for consumers. The purpose of this study was to determine the effect of Phyllanthus niruri and Andrographis paniculata extracts on egg yolk index and haugh units (HU) value in laying hens with Avian Pathogenic Escherichia coli. This type of study was experimental using a complete randomized design with 100 experimental units of five treatments (P-) placebo, (P+) infected with Avian Pathogenic E. coli without P. niruri and A. paniculata extract, then groups of chickens infected with Avian Pathogenic E. coli and administration of (P1) 10% of P. niruri and 30% of A. paniculata, (P2) 20% of P. niruri and 20% of A. paniculata, (P3) 30% of P. niruri and 10% of A. paniculata then egg yolk index and HU value were evaluated. The data obtained were analyzed using ANOVA followed by Duncan's test. The results showed a significant difference between the treatment groups based on the egg yolk index and the HU value. It can be concluded that P2 can be recommended for laying hens with avian pathogenic E. coli.